Human Resource Optimization in School Health and Physical Education Programs in Islamic Education - Arifin, Slamet; Pranitasari, Diah (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2025)
Islamic education institutions are increasingly expected to realize their educational vision while simultaneously strengthening students' health, physical fitness, and holistic well-being. This study examines how human resource (HR) optimization supports the realization of the Islamic education vision through School Health (UKS) and Physical Education (PE) programs at the Daarul Arifin Indonesia Foundation. Employing a qualitative case study design, data were collected through in-depth interviews with foundation leaders, principals, teachers, and school health personnel; direct observation of UKS and PE implementation; and document analysis of strategic plans, program reports, and standard operating procedures. The data were analyzed using thematic analysis to identify patterns of HR planning, development, coordination, and performance management related to health and PE initiatives. Findings indicate that HR optimization is reflected in: (1) alignment of HR policies with the institution's Islamic educational vision and student well-being goals; (2) capacity building for teachers and staff in health literacy, safe physical activity practices, and value-based character formation; (3) cross-unit collaboration between academic staff, UKS teams, and external health partners; and (4) monitoring and evaluation mechanisms that integrate spiritual, behavioral, and health-related outcomes. Key challenges include uneven staff competencies, limited facilities, and inconsistent program documentation. The study proposes an integrative HR governance approach that connects faith-based educational objectives with sustainable school health and PE management, offering practical implications for Islamic foundations seeking to strengthen educational quality through student well-being.